Government transfers, COVID-19 shock, and food insecurity: Evidence from rural households in India - Kumar, Anjani; Mishra, Ashok K.; Saroj, Sunil; Rashid, Shahidur (Wiley, 2022)
The coronavirus disease 2019 (COVID-19) pandemic has decimated the lives and livelihoods of people worldwide. The impact of COVID-19 has been especially devastating for low-income families in rural areas of India. Soon after the nationwide lockdown was announced, food insecurity became pervasive in rural areas, as many families relied on daily wage work to fund necessities. By providing cash transfers and additional foodgrains, Indian policymakers acted swiftly to reduce the financial impact on family income and consumption. This paper investigates the factors affecting rural families' participation in the cash transfer program and the effect of government cash transfers on food insecurity. Results indicate that India's government cash transfer program decreased moderate food insecurity by 2.4% and severe food insecurity by about 0.92%.